2012
DOI: 10.1002/stem.1091
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Directly Differentiated from Partially Reprogrammed Fibroblasts Rapidly Acquire Gliogenic Competency

Abstract: Neural stem cells (NSCs) were directly induced from mouse fibroblasts using four reprogramming factors (Oct4, Sox2, Klf4, and cMyc) without the clonal isolation of induced pluripotent stem cells (iPSCs). These NSCs gave rise to both neurons and glial cells even at early passages, while early NSCs derived from clonal embryonic stem cells (ESCs)/ iPSCs differentiated mainly into neurons. Epidermal growth factor-dependent neurosphere cultivation efficiently propagated these gliogenic NSCs and eliminated residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 62 publications
1
75
0
Order By: Relevance
“…Thus, methods for reprogramming toward certain region-specific NPCs remain to be developed. Similar to previous studies (7,10,33), our iNPCs preferentially differentiated into astrocytes. Considering that BAM are neurogenic genes, preferential astrocytic differentiation is unexpected.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, methods for reprogramming toward certain region-specific NPCs remain to be developed. Similar to previous studies (7,10,33), our iNPCs preferentially differentiated into astrocytes. Considering that BAM are neurogenic genes, preferential astrocytic differentiation is unexpected.…”
Section: Discussionsupporting
confidence: 89%
“…However, in doing so, they largely lost the reprogramming efficacy, cell expandability/renewability (9,14), or the competence to generate myelin-forming cells in vitro or in vivo (11,(13)(14)(15)(21)(22)(23). It has been reported that reprogramming of fibroblasts to NPCs could be achieved using a single transcription factor, SOX2 (11).…”
Section: Discussionmentioning
confidence: 99%
“…To more rapidly induce NSCs from somatic cells, we generated NSCs from adult mouse fibroblasts that were partially reprogrammed by the introduction of the four Yamanaka factors (OSKM), which directs their differentiation into neural lineages 16) .…”
Section: Nscs Directly Induced From Fibroblastsmentioning
confidence: 99%